Factors Affecting the Development and Hatching of Eggs and the Survival of Infective Larvae of Haemonchus contortus in Laboratory Condition (Progressive Agriculture, 2013)
Haemonchus contortus Rudolphi, 1803, a blood-sucking worm living in abomasum, poses possibly the greatest threat to the livestock production. Here, we studied the effects of various environmental and nutritional factors on the development and hatching of eggs, development and survival of larvae of H. contortus.  We incubated eggs at different temperature gradients, humidity and pH in phosphate buffer saline (PBS), tap water (TW) and normal saline (NS) using serum and/or liver extract at different concentrations.  We obtained maximum hatching of eggs (39.73%) at 26ºC by day 5. Moulting started from day 4 and maximum number of L2 (23.11%) developed at day 5 at 26ºC and the highest number of L3 (26.81%) were detected at day 7 at 26ºC. No developments of eggs were observed, and hatching did not occur at pH 2. Better hatching of eggs (43.84%) were recorded in the relative humidity (RH) of ³ 80-90%. Light had no significant effects on the development and hatching of eggs of H. contortus. Maximum eggs hatched in PBS containing 15% serum and 10% liver extract. Besides, in this medium survival rate of larvae was the highest (39.51%). The present study suggests that PBS containing 15% serum and 10% liver-extract may be used as a suitable medium for the incubation of eggs of H. contortus.DOI: http://dx.doi.org/10.3329/pa.v22i1-2.16469 Progress. Agric. 22(1 & 2): 75-83, 2011